Systematic Literature Review: The Trend of English for Midwifery Teaching Material in The Digital Era - Nuranisa, Nisa; Gailea, Nurhaeda; Juniardi, Yudi (PPSDP International Journal of Education, 2023)
This study aims to conduct a literature review related to the trend of English for midwifery teaching material in the digital era. The research method used in this study is the SLR (Systematic Literature Review) method. Data collection is done by documenting articles that have similar research. The articles used were 12 national journals indexed by Google Scholar published period 2011-2023. Based on this research, it was found that midwifery English teaching materials are in the form of printed and digital teaching materials. 58% printed midwifery English teaching materials are in the form of booklets, modules, pocket books and textbooks. 42% Digital midwifery English teaching materials in the form of web, android, duolingo applications and google classroom application. Based on the SWOT analysis that has been carried out, there are weaknesses in the existing midwifery English teaching materials, namely that they are less supportive when used independently by students without being accompanied by a teacher and require other technology to access them. Therefore, improvements should be made in the development of midwifery English teaching materials so that they can help students understand the material optimally. This research is expected to provide additional knowledge for ESP English lecturers, especially in the field of midwifery, so as to increase the creativity and quality of lecturers in making midwifery English teaching materials. This research qualifies, elaborates and describes previous research regarding the trend of English for midwifery teaching material in the digital era, based on the searches that have been done no one has conducted this research.